2022
DOI: 10.1038/s41598-022-10926-1
|View full text |Cite
|
Sign up to set email alerts
|

Apigeninidin-rich Sorghum bicolor (L. Moench) extracts suppress A549 cells proliferation and ameliorate toxicity of aflatoxin B1-mediated liver and kidney derangement in rats

Abstract: Sorghum bicolor plant has a high abundance of 3-deoxyanthocyanins, flavonoids and other polyphenol compounds that have been shown to offer numerous health benefits. Epidemiological studies have linked increased intake of S. bicolor to reduced risk of certain cancer types, including lung adenocarcinoma. S. bicolor extracts have shown beneficial effects in managing hepatorenal injuries. This study investigated the cytotoxic potential of three apigeninidin-rich extracts of S. bicolor (SBE-05, SBE-06 and SBE-07) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 108 publications
(115 reference statements)
2
28
0
Order By: Relevance
“…(Li et al, 2022) results showed obvious necrotic characteristics, including cell swelling, rupture of cell and mitochondrial membranes and inflammation in chicken livers. (Owumi et al, 2022) In this study, the liver and kidneys of AFB1-deficient mice showed evidence of focal inflammatory cell infiltration, mild water/balloon hepatocyte degeneration and moderate vesicular steatosis. (Papiya, 2005) indicated that the metabolic products of A.fungus .flavus led to the occurrence of vascular congestion in the liver.…”
Section: Histopathological Observations To Clarify the Protective Eff...mentioning
confidence: 49%
“…(Li et al, 2022) results showed obvious necrotic characteristics, including cell swelling, rupture of cell and mitochondrial membranes and inflammation in chicken livers. (Owumi et al, 2022) In this study, the liver and kidneys of AFB1-deficient mice showed evidence of focal inflammatory cell infiltration, mild water/balloon hepatocyte degeneration and moderate vesicular steatosis. (Papiya, 2005) indicated that the metabolic products of A.fungus .flavus led to the occurrence of vascular congestion in the liver.…”
Section: Histopathological Observations To Clarify the Protective Eff...mentioning
confidence: 49%
“…Following kidney injury, these metabolites accumulate in the bloodstream due to impaired excretion, and if this is not remedied, it can trigger renal failure. The implications of ALT, AST, ALP, GGT, urea, and creatinine in acute/chronic liver and kidney diseases have been reported previously [ 11 , 48 , 65 , 73 ].…”
Section: Discussionmentioning
confidence: 75%
“…As a resolvin, IL-10—an anti-inflammatory cytokine- suppresses pro-inflammatory responses [ 72 ]. Still, where the expression of IL-10 is dampened, as seen in this study, the hepatic and renal tissue is exposed to more inflammatory insults, leading to hepatorenal derangements [ 73 ]. The involvement of Pb and Furan in mediating inflammation and oxidative stress in rats' liver and kidneys have been previously studied in rats [ 12 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we have shown that API suppressed STAT3 activation. 79 The combination of STAT3 signaling inhibition and API's anti-inflammatory and antioxidant effects (Figure 9) could explain its ameliorative effects on the toxicity of AFB1 to the male reproductive system.…”
Section: Discussionmentioning
confidence: 99%